2022
DOI: 10.3390/polym14142790
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Melt Processing Conditions on the Degradation of Polylactic Acid

Abstract: To reduce the degradation of polylactic acid (PLA) during processing, which reduces the molecular weight of PLA and its properties, prior studies have recommended low processing temperatures. In contrast, this work investigated the impact of four factors affecting shear heating (extruder type, screw configuration, screw speed, and feed rate) on the degradation of PLA. The polylactic acid was processed using a quad screw extruder (QSE) and a comparable twin screw extruder (TSE), two screw configurations, higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…For calculations of the heat involved in the processes and the melting and crystallization temperatures that occurred during heating and cooling, TA60WS software (Kyoto, Japan) was used. The calculation of polymer crystallinity was also performed using Equation (1), conceived by Rossin and Aldhafeeri [ 25 , 26 ]. X c = (Δ H m − Δ H c /Δ H ° m ) × 100 where X c is the degree of crystallinity of the polymer, Δ H cc is cold crystallization enthalpy of the sample, Δ H m is fusion enthalpy of the sample, Δ H° m is theoretical fusion enthalpy of the 100% crystalline sample; in the case of PBAT, Δ H° m = 114 J·g −1 , and, for PLA, Δ H° m = 93.7 J·g −1 .…”
Section: Methodsmentioning
confidence: 99%
“…For calculations of the heat involved in the processes and the melting and crystallization temperatures that occurred during heating and cooling, TA60WS software (Kyoto, Japan) was used. The calculation of polymer crystallinity was also performed using Equation (1), conceived by Rossin and Aldhafeeri [ 25 , 26 ]. X c = (Δ H m − Δ H c /Δ H ° m ) × 100 where X c is the degree of crystallinity of the polymer, Δ H cc is cold crystallization enthalpy of the sample, Δ H m is fusion enthalpy of the sample, Δ H° m is theoretical fusion enthalpy of the 100% crystalline sample; in the case of PBAT, Δ H° m = 114 J·g −1 , and, for PLA, Δ H° m = 93.7 J·g −1 .…”
Section: Methodsmentioning
confidence: 99%
“…At a higher screw rotation speed, the residence time and thus the exposure of PLA to high temperature and shear inside the extruder is shorter, resulting in reduced degradation. In the work of Atalay et al [86], a lower complex viscosity was reported when amorphous PLA was processed at 50 rpm than at 100 rpm, both at a processing temperature of 150 • C. In addition, Aldhafeeri et al [90] reported η 0 -values of 4806 Pa•s at 400 rpm and 5332 Pa•s at 1000 rpm due to the longer residence time at lower screw rotation speeds. As indicated before in the works of Mysiukiewicz et al [79] and Taubner and Shishoo [89], it is important to take the processing temperature into account when evaluating the effect of screw rotation speed.…”
Section: Influence Of Screw Rotation Speedmentioning
confidence: 97%
“…Contradictory results about the influence of screw rotation speed on the degradation are found in the literature. Most articles [79,86,89,90] concluded that an increase in screw rotation speed resulted in a smaller decrease in molecular weight (see Figures 16 and 17), which can be explained by a shorter residence time. At a higher screw rotation speed, the residence time and thus the exposure of PLA to high temperature and shear inside the extruder is shorter, resulting in reduced degradation.…”
Section: Influence Of Screw Rotation Speedmentioning
confidence: 99%
“…The influence of single extrusion, multiple extrusion, AM, and injection molding on polymeric degradation has been broadly studied in the past decades. For instance, degradation has been assessed for PLA and PLLA [167,[173][174][175][176], poly(ethylene terephthalate) (PET) [177,178], PS [42,[179][180][181], ABS [182][183][184], HIPS [185][186][187], PP [93,151,159,[188][189][190][191], HDPE [139,188,192], LDPE [140], and poly(methyl methacrylate) (PMMA) [42]. To highlight the advances made, an overview of the most important findings is given in this section.…”
Section: Manufacturing Case Studies To Assess Degradabilitymentioning
confidence: 99%
“…Structural changes were monitored via rheological measurements, perceived by the significant decrease in the zero-shear viscosity under these conditions. Aldhafeeri et al [175] discussed that the processing parameters which increase the residence time, i.e., lower screw rate, lower feed rates, a quad screw extruder, and kneading blocks, result in a more pronounced degradation of PLA, confirmed by the reduction in the zero-shear viscosity. Additionally, the PLA grades with a low starting viscosity were less susceptible to degradation than the ones with a high starting viscosity at higher screw speeds [174].…”
Section: Manufacturing Of Polyestersmentioning
confidence: 99%